STUDY OF VARIOUS FIVE EXTRACTS OF TRACHYSPERMUM AMMI SEEDS ON SELECTED FOUR GRAM-NEGATIVE COOKED FOOD SPOILAGE BACTERIAL STRAINS BY DISK DIFFUSION METHOD - Masih, Usha (International Journal of Research -GRANTHAALAYAH, 2015)
Bacterial foodborne diseases are caused by consumption of foods contaminated with bacteria or their toxins. This study evaluated antibacterial properties of Trachyspermum ammi Acetone, ethanol, methanol, cold water and hard water extracts of spice (Ajowan) seeds against four gram negative strains of pathogenic foodborne bacteria, E. coli O157:H7 ATCC 43888, ATCC 25922, ATCC 8739 and ATCC 43895 that cause infection and intoxication. E. coli ATCC 43888 was observed to be highly susceptible to all extracts of ajowan with absolute zones of inhibition in the range of 16mm – 23mm in diameter. This study demonstrated that spice extracts have antimicrobial activity against food-borne bacterial species and should be considered as potential antibacterial agents for addition to ready meals. The spice contain high amount of secondary metabolites due to these metabolites they have high antimicrobial activity and it can be used as good bio- preserver and it can also use for medicinal purpose.